Large and stable: actin aster networks formed via entropic forces - Spukti, Friedrich Fabian; Schnauß, Jörg (Frontiers in Chemistry, 2022)
Biopolymer networks play a major role as part of the cytoskeleton. They provide stable structures and act as a medium for signal transport. These features encourage the application of such networks as organic computation devices. While research on this topic is not advanced yet, previous results are very promising. The protein actin in particular appears advantageous. It can be arranged to various stable structures and transmit several signals. In this study aster shaped networks were self-assembled via entropic forces by the crowding agent methyl cellulose. These networks are characterised by a regular and uniquely thick bundle structure, but have so far only been accounted in droplets of 100 \textmu m diameter. We report now regular asters in an area of a few mm2 that could be observed even after months. Such stability outside of an organism is striking and underlines the great potential actin aster networks display.